Effectiveness of rational emotive behavior therapy group counseling to improve students’ self-confidence - Lathifa, Auladina; Syukur, Yarmis; Asnah, Megaiswari Biran; Nurfarhanah, Nurfarhanah (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research was motivated by a phenomenon at SMA Pertiwi 1 Padang, where as many as 16 out of 171 students had self-confidence in the low category. This study aimed to prove the role of group counseling with a rational emotive behavior therapy (REBT) approach in increasing students’ self-confidence. This quantitative experimental research has a sample of 20 students divided into experimental and control groups. The sampling technique uses purposive sampling. Data were analyzed using the Wilcoxon signed rank test and Kolmogorov Smirnov 2 independent samples. The study results stated that students’ self-confidence was in the medium category, with a percentage of 76.6%. The self-confidence of the experimental group students before being given REBT group counseling averaged 72.2 in the low category, and after being given REBT group counseling treatment increased to 125.6 in the high category. The self-confidence level of the control group students before being given group guidance without REBT was 84.5 in the low category. After being given counseling treatment, the REBT group increased to 104.7 in the medium category. REBT group counseling has effectiveness in increasing students’ self-confidence.